Inovasi Nilai Tambah dan Daya Saing Produk BUMDes Pokdakan Naminasang Farm melalui Pendampingan PIRT dan Sertifikasi Halal - Budiantoro, Harry; Santosa, Perdana Wahyu; Suhaeri, Suhaeri; Putri, Arimbi Eka; Salsabila, Aulia Zikra (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2025)
This Community Service Program aims to increase the added value and competitiveness of products from the Village-Owned Enterprise (BUMDes) POKDAKAN NaminaSang Farm & Co in Mandalamekar Village by assisting in obtaining Home Industry Food Permits (PIRT) and halal certification were carried out on August 3, 2025. The methods used include training, outreach, coaching, and intensive consultations for POKDAKAN members. The community service team also collaborates with halal certification institutions and local health departments. Activities include education on licensing procedures, training halal supervisors, and assistance with PIRT permit applications. Initial results show a significant increase in partners' understanding of PIRT and halal regulations, as well as their readiness to process permits. Partner products that have gone through the standardization and certification process are expected to be able to penetrate modern markets and large retailers, while increasing consumer confidence. This program aligns with the Sustainable Development Goals (SDGs), particularly in the aspects of community welfare, health, and partnerships.